PPM1A and PPM1B act as IKKβ phosphatases to terminate TNFα-induced IKKβ-NF-κB activation - Sun, Wenjing (2008)
IKKβ serves as a central intermediate signaling molecule in the activation of the NF-κB pathway. However, the precise mechanism for the termination of IKKβ activity is still not fully understood. Using a functional genomic approach, we have identified two protein serine/threonine phosphatases, PPM1A and PPM1B, as IKKβ phosphatases. Overexpression of PPM1A or PPM1B results in dephosphorylation of IKKβ at Ser177 and Ser181 and termination of IKKβ-induced NF-κB activation. PPM1A and PPM1B associate with the phosphorylated form of IKKβ, and the interaction between PPM1A/PPM1B and IKKβ is induced by TNFα in a transient fashion in the cells. Furthermore, knockdown of PPM1A and PPM1B expression enhances TNFα-induced IKKβ phosphorylation, NF-κB nuclear translocation and NF-κB-dependent gene expression. These data suggest that PPM1A and PPM1B play an important role in the termination of TNFα-mediated NF-κB activation through dephosphorylating and inactivating IKKβ.